Virtual EI - Schnaubelt, Teri; Marvel, Steve (Ascent Audio, 2023)
Be mindful, empathetic, and authentic-even on-screen. Managing your team, building relationships and trust, and facilitating effective meetings in a hybrid or fully remote workforce is challenging. Virtual EI explores how to develop, practice, and demonstrate your emotional intelligence and social skills in a virtual or hybrid setting. You'll learn how to make your team feel heard, draw everyone's voice into the conversation, and make real connections. This volume includes the work of Amy C. Edmondson, Mark Mortensen, Heidi K. Gardner, and Amanda Sinclair. How to be human at work. The HBR Emotional Intelligence series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.
Online resource; title from title details screen (O'Reilly, viewed June 13, 2023)
Keywords: Emotional intelligence; Virtual work; Telecommuting; Work environment -- Psychological aspects; Virtual work teams; Intelligence émotionnelle; Travail virtuel (Mécanique analytique); Équipes virtuelles; Work environment; Psychological aspects; Audiobooks; Livres audio